Kebijakan Publik Dalam Meningkatkan Pelayanan Sebagai Implementasi Otonomi Daerah Di Kota Denpasar - I Nyoman Artayasa (Jurnal Ilmiah Cakrawarti, 2019)
Policy of regional autonomy was born with the aim to keep the government and the integrityof the Unitary Republic of Indonesia (NKRI), by encouraging the ability of initiative and creativity oflocal government and local communities in the pursuit of prosperity. Public Policy is whatevergovernments choose to do or not todo. The principle of public service is to provide a service with agood quality to the community which embodies the obligation of the government apparatus as a publicservant . Regional autonomy gives authority to local government in this case the city government toexplore potential areas to improve the quality of service to the community. In providing good serviceto the community, Denpasar government adopt local wisdom that philosophy Sewaka Dharma. SewakaDharma can be defined as "Serving is the obligation."